The Urgency of Digital Literacy in Indonesia on COVID-19 pandemic - Williams, Alexander; Bangun, Cicilia Sriliasta; Shino, Yamato (Pandawan Sejahtera Indonesia, 2022)
For pupils, having a strong grasp of digital literacy is crucial, particularly in light of the COVID-19 pandemic. Every level of society is encouraged to have simple access to the internet by the use of distant learning. In this essay, we will investigate the state of digital literacy in Indonesia at the time of COVID-19 epidemic. A systematic review was used as the research methodology in this study. Campaigns to promote digital literacy are crucial during the COVID-19 epidemic, according to the research findings. Dealing with the COVID-19 outbreak will be made easier with the help of digital literacy. During the COVID-19 epidemic, the digital literacy movement will assist the general people in finding the appropriate information and passing the time. The following are other crucial elements in the development of digital literacy. 1) Understanding culture, namely the diverse contexts in which users of the digital world operate; 2) Cognitive, or the capacity for cognition when evaluating the content;three) constructive Communication, specifically an awareness of network and communication performance in the digital age, self-assurance in one's ability to act responsibly, creativity—doing things differently—critical thinking about content, and social responsibility.